Pengembangan Media Pembelajaran Berbasis Aplikasi Nisila Nilai Pancasila untuk Siswa Kelas V Sekolah Dasar - Winda Rahayuningtiyas; Ilmawati Fahmi Imron; Endang Sri Mujiwati (Jayapangus Press, 2023)
This research was obtained from observations as well and interviews conducted at SDN Mrican 1 Kediri City, where it is known that the use of media in learning Civics, particularly the Pancasila Values material, is still very limited. As a result, it is critical to create media that is engaging, innovative, and capable of engaging students in their learning. The goals of this study were to 1) describe the validity of interactive multimedia Nisila, 2) describe its effectiveness, and 3) describe teachers' and students' reactions to the development of interactive multimedia Nisila. The research method used in this study is R&D using the ADDIE model, which has five stages: 1) Analyze, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The validation of the media construction received an 89% score, while the validation of the media material received an 88% score. The effectiveness of Nisila's interactive multimedia received an average score of 92 in the limited test and a score of 92.5 in the broad test. The teacher's response to Nisila's interactive multimedia is 90%, and the student response is 98%. Based on these findings, it is possible to conclude that Nisila's interactive multimedia is highly valid, effective, and widely used.